Quantification of Facial Geometrical Dimension for Student Attendance Tracking (International Journal of Innovative Computing, 2024)
The traditional method of manual attendance-taking has been used in educational institutions for decades which have consumed one-sixth amount of class time for attendance marking. Great research on attendance systems has come up with techniques like biometrics, NFC’s and QR codes. Moreover, with advancements in technology, this research project can provide a more efficient and effective solution. This research project utilizes image processing, computer vision and facial recognition technology to mark the attendance of the students in class. The objectives of the system are registration of facial image, perform landmarking of the facial image and develop automated attendance system. As a result, this project works by installing a camera on top of the board which detects the student faces and performs attendance marking. Now is the time to implement this system in schools, institutions, colleges, and universities to streamline the attendance-taking process. This automated system will not only save time and effort but will also provide accurate attendance records, which will benefit both management and students.
Keywords: Attendance System, image processing, automated attendance, facial biometric, facial recognition, computer vision, facial landmarking, encoding facial geometry